2002
DOI: 10.4049/jimmunol.168.9.4601
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of Apoptosis-Inducing and Preventing Signals in Bacteria-Faced Macrophages Through Myeloid Differentiation Factor 88 and IL-1 Receptor-Associated Kinase Members

Abstract: The induction of apoptosis in host cells is a common strategy by which pathogenic bacteria interfere with the host immune response. The Yersinia enterocolitica outer protein P (YopP) inhibits activation of transcription factor NF-κB in macrophages, which suppresses NF-κB-dependent antiapoptotic activities. The simultaneous initiation of proapoptotic signaling by yersiniae infection or LPS treatment results in macrophage apoptosis. In this study, we used YopP as a tool to dissect survival- and death-inducing pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 67 publications
7
64
2
Order By: Relevance
“…Thus, even in case of reduced chemotactic activity in peritoneal cavities of MyD88-deficient mice attenuation of leukocyte apoptosis might compensate for diminished cell recruitment. Accordingly, TLR-and MyD88-mediated signals are well known to trigger apoptosis of leukocytes and other cell types [45][46][47][48][49][50]. Moreover, our previous work [51] has shown that attenuation of TLR responsiveness through induction of in vivo LPS tolerance results in diminished neutrophil apoptosis and enhanced peritoneal neutrophil accumulation during septic peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even in case of reduced chemotactic activity in peritoneal cavities of MyD88-deficient mice attenuation of leukocyte apoptosis might compensate for diminished cell recruitment. Accordingly, TLR-and MyD88-mediated signals are well known to trigger apoptosis of leukocytes and other cell types [45][46][47][48][49][50]. Moreover, our previous work [51] has shown that attenuation of TLR responsiveness through induction of in vivo LPS tolerance results in diminished neutrophil apoptosis and enhanced peritoneal neutrophil accumulation during septic peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…TLR2-dependent apoptotic signaling is coupled to the cell death machinery through activation of MyD88 and FADD (47), a cytotoxic pathway that is potentially also involved in Yersinia-mediated apoptosis (48,62). MyD88 binds to the TLR2 intracellular signaling domain and recruits FADD through death domain-death domain interaction (47).…”
Section: Discussionmentioning
confidence: 99%
“…None of the overexpressed constructs induced substantial cell death in the absence of MG-132 (Ref. 48; data not shown).…”
Section: A Role Of Fadd In the Tlr4-activated Apoptotic Pathwaymentioning
confidence: 93%
See 1 more Smart Citation
“…[33][34][35]64 Nevertheless, the highest levels of apoptosis are achieved by combination cytokine provision, 7,44,63 suggesting that TNFa could sensitize cells to the effects of IL-1b or could prime these cells for IRAK-mediated signaling. 21,22,[65][66][67][68][69] Although TNFR-Ig confers protection to human islets from TNFa effects, it was not effective in completely preventing apoptosis activation in culture, as measured by Annexin V staining in FACS analysis. This is not unexpected in the light of the preceding discussion.…”
Section: Discussionmentioning
confidence: 99%